1999
DOI: 10.1002/(sici)1097-0215(19990412)81:2<180::aid-ijc3>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and conditional cadherin expression in cultured human ovarian surface epithelium: Influence of family history of ovarian cancer

Abstract: Epithelial ovarian carcinomas arise in a simple mesothelium (ovarian surface epithelium, OSE) but exhibit properties of oviductal and endometrial epithelia. Thus, during malignant progression, their differentiation proceeds from simple to complex, in contrast to carcinomas in other tissues. Related changes in OSE of women with a history of familial ovarian cancer indicate that this aberrant differentiation is initiated very early in neoplastic progression. The mechanisms underlying this process are not underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…OSE cells possess primary cilia, as visualized with antibodies against two well-characterized ciliary markers, acetylated α-tubulin (Acet.tub) and detyrosinated α-tubulin (Glu.tub) (Figure 1A, lower insert) as described earlier [56]. Further, consistent with previous observations [57-59], we found that OSE has a limited commitment to the epithelial phenotype indicated by the retention of mesenchymal features, such as expression of vimentin and N-cadherin, and it lacks some of the typical epithelial characteristics, such as E-cadherin (Figure 1B-D).…”
Section: Resultssupporting
confidence: 91%
“…OSE cells possess primary cilia, as visualized with antibodies against two well-characterized ciliary markers, acetylated α-tubulin (Acet.tub) and detyrosinated α-tubulin (Glu.tub) (Figure 1A, lower insert) as described earlier [56]. Further, consistent with previous observations [57-59], we found that OSE has a limited commitment to the epithelial phenotype indicated by the retention of mesenchymal features, such as expression of vimentin and N-cadherin, and it lacks some of the typical epithelial characteristics, such as E-cadherin (Figure 1B-D).…”
Section: Resultssupporting
confidence: 91%
“…However, during embryogenesis, neuro crest cell migration is initiated by the down-regulation of N-cadherin [28], therefore, the N-cadherin level is not the sole determinant of the cell migratory phenotype in all processes. Consistent with this notion, an N to E-cadherin switch occurs in ovarian cancer [29], [30] while the expression of cadherin 11 has been shown to suppress cell migration [31]. Ectopic expression of new cadherins along with other cadherin regulators may be the key to controlling cell-cell adhesion of migratory cells.…”
Section: Discussionmentioning
confidence: 91%
“…It is widely accepted that an increased expression of E-cadherin in cancer is associated with a better outcome and a decrease occurrence of metastases [13]; in ovarian carcinoma lower E-cadherin seems to influence the transition from normal ovarian surface epithelium to ovarian cancer [36]. The investigation of KSP-cadherin showed only a weak membranous and cytoplasmic expression in both subtypes of papillary RCC.…”
Section: Discussionmentioning
confidence: 99%